Atividade da polifenoloxidase em camarão(Litopenaeus vannamei) submetido ao emprego do frio e atmosfera modificada. - Oliveira, Lucivânia Assis de (2013)
After despesca shrimp is highly perishable, with a shelf life limited due to the occurrence of melanosis and microbial contamination. The melanosis is triggered by a biochemical mechanism that oxidizes phenols to quinones by the enzyme polyphenol oxidase (PPO). Quinones in turn react non-enzymatically with other compounds forming dark melanin pigments responsible for melanosis. Although not damaging to consumer health, melanosis dramatically reduces the commercial value of the shrimp. The aim of this study was to evaluate the enzymatic activity of PPO shrimp Litopenaeus vannamei subjected to freezing, modified atmosphere and cooling in ice for their respective stores. Samples were obtained in trading environment, packed and transported to the Laboratory of Technology and Processing Meat and Fish (LTPCP / DEA / UFPB). The products were made from whole shrimp and subsequently submitted to the following treatments: the domestic freezer (-18 ± 1 ° C) - FREEZER; tunnel freezing at (-35 ° C) - TUNNEL, liquid nitrogen (-86 ° C) - NITROGEN; cooling on ice - ICE; Modified Atmosphere (75% CO2 / 25% O2) - AM1, Modified Atmosphere (25% CO2 / 75% O2) - AM2 and Vacuum Packaging - VOID. The samples were stored subjected to freezing (-18 ° C) for 90 days, and the samples cooled on ice and modified atmosphere were stored for 9 days. The vacuum packaging liquid nitrogen and were more effective in inhibiting PPO activity, and delayed melanosis during storage. The color parameters pH, shear force and water activity have changed over time, both in frozen samples as in chilled.